Three-Dimensional DNA Nanomachine Biosensor by Integrating DNA Walker and Rolling Machine Cascade Amplification for Ultrasensitive Detection of Cancer-Related Gene - Wu, Na; Wang, Kun; Wang, Yi-Ting; Chen, Ming-Li; Chen, Xu-Wei; Yang, Ting; Wang, Jian-Hua (Analytical chemistry (Washington), 2020)
Stochastic DNA walkers capable of traversing on three-dimensional (3D) tracks have received great deal of attention. However, DNA walker-based biosensors exhibit limited amplification efficiency because of their slow walking kinetics and low processivity. Herein, by taking advantage of the high processivity of a DNA rolling machine, a sensitive ratiometric DNA nanomachine biosensor is designed. The biosensor is constructed with hairpin-loaded Au nanoparticles (NPs) (hpDNA@AuNPs) as a DNA walker and AgNCs-decorated magnetic NPs (AgNCs@MNPs) as a DNA rolling machine. In the presence of target DNA, exonuclease III (Exo III)-powered DNA walker is activated to accomplish first-stage amplification via a burnt-bridge mechanism, generating a great deal of toehold-loaded AuNPs (Toehold@AuNPs) to hybridize with magnetic nanoparticles loaded with silver-nanoclusters-labeled DNA (AgNCs@MNPs) with the assistance of Exo III. These trigger rapid rolling of AuNPs on the AgNCs@MNPs surface and release free AgNCs, converting the biological signal into a mass spectrometric signal ratio (107Ag/197Au) with detection by ICP-MS. A linear range of 0.5–500 fmol L–1 is achieved with a detection limit of 119 amol L–1 for the p53 gene. The practical applicability of the biosensor has been demonstrated in the accurate assay of the p53 gene in the human blood.